In-Person Education During the Early COVID-19 Pandemic at Wichita Collegiate School : In person learning at WCS during COVID - Mantovani, Emma; Meyer, Christopher; Sandid, Adam; weeks, Kerri; Dedeaux, Julian; assi, maha (Kansas Journal of Medicine, 2022)
Introduction. The COVID-19 pandemic forced most schools in Kansas in 2020-2021 to adopt remote or hybrid learning. Wichita Collegiate School proceeded with an in-person teaching model. The purpose of this study was to determine if in-person learning can be done safely during the COVID-19 pandemic prior to vaccine use. Methods. Wichita Collegiate is a private school located in Sedgwick County, Kansas. The study population included 671 students (grades 1-12) and 130 staff. The procedures implemented during the school year (8/19/20- 5/21/21) included: mandatory face coverings, six feet physical distancing, and daily temperature checks. A registered nurse performed contact tracing and executed quarantine requirements per the Center for Disease Control and Prevention (CDC) guidelines. Results. Over the study period, 487 students and staff were tested for COVID-19, and 18.5% (n=90) were positive. Overall, students and staff rate of COVID 19 infection was lower than the expected rate when compared to the surrounding community of Sedgwick County. Thorough contract tracing of positive cases revealed that 2.2% (n=2) individuals were likely exposed to COVID-19 at school. Conclusions. This study suggests that transmission of COVID-19 was infrequent in a school setting with in-person attendance, even before widespread vaccine availability. By following public health guidelines and utilizing contact tracing, this study suggests that it is possible to limit the spread of COVID-19 during in-person learning. This has immediate implications for how schools safely returned to in-person learning in the post vaccine era.